1985
DOI: 10.1111/j.1471-6402.1985.tb00898.x
|View full text |Cite
|
Sign up to set email alerts
|

Age and Gender Dimensions of Friendship

Abstract: Since stereotypes about appropriate social behavior appear to influence questionnaires and other self-reported data concerning friendship, an in-depth interview format was used to explore gender and age differences in friendship patterns. Thirty-one subjects were interviewed: five young males, six young females, five midlife males, five midlife females, five older males, and five older females. As in our previous questionnaire studies, groups described friendship in superficially similar ways. However, in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
2
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 11 publications
2
28
2
1
Order By: Relevance
“…This result disagrees with results of these studies: [57]). The result of the current study disagrees with results of previous studies which indicated that there are differences in friendship due to age.…”
Section: Resultscontrasting
confidence: 57%
See 1 more Smart Citation
“…This result disagrees with results of these studies: [57]). The result of the current study disagrees with results of previous studies which indicated that there are differences in friendship due to age.…”
Section: Resultscontrasting
confidence: 57%
“…There are studies that have indicated differences in friendship skills due to age (Kuhne, 1999 [57]). Kuhne's study (1999) [8] indicates that friendship in adolescence is more stable than in childhood.…”
Section: Friendship and Agementioning
confidence: 99%
“…This awareness of and concern for`others' ®ts feminine stereotypes, where females typically are seen as more aware of other's feelings and needs, and as better able to see the perspective of others (e.g., Carey et al, 1988;Davis, 1983;Dobbins, 1985;Fox et al, 1985;Hanson and Mullis, 1985;Rosnowska, 1985;Santilli and Hudson, 1992). This stereotype is consistent with the stronger association of empathy and perspective taking of females as opposed to males (Davis, 1983;Litvack-Miller et al, 1997).…”
Section: The Second Dimension Is Courtesymentioning
confidence: 96%
“…Implicit in this characterization is the notion that instrumental behaviors are self-oriented, while expressive behaviors are other-oriented (de Beauvoir, 1952;Flax, 1983;Gilligan, 1982;Gilligan et al, 1988). In general, the expressive end of the continuum is exempli®ed by stereotypically feminine traits and behaviors such as empathy, perspective taking, concern for others (e.g., Carey et al, 1988;Dobbins, 1985;Eagly and Karau, 1991;Fox et al, 1985;Hanson and Mullis, 1985;Rosnowska, 1985;Santilli and Hudson, 1992), altruism and helping, (Gilligan et al, 1988;Held, 1990;Ridgeway, 1991), and emotionality (Stoppard and Grunchy, 1993). In contrast, the instrumental end of the continuum is exempli®ed by stereotypically masculine traits such as competitiveness, aggression, and ambition (Berger et al, 1980;Ely, 1994;Lockheed and Hall, 1976;Meeker and Weitzel-O'Neill, 1977;Schein and Mueller, 1992).…”
Section: Gender Rolesmentioning
confidence: 97%
“…As gender 62,63 and age 64 differences are often found on gamerelated issues, and can influence the size of one's friendship circle, 65,66 these variables were held as covariates in all of the following analyses.…”
Section: Between-group Analysesmentioning
confidence: 99%